2020
DOI: 10.1002/smr.2266
|View full text |Cite
|
Sign up to set email alerts
|

Global software development governance: Challenges and solutions

Abstract: Global software development (GSD) has become a rising software development model in the last few years. Although much research has been performed in terms of GSD management, GSD governance research is scarce at the present time and presents multiple challenges that need to be addressed. In this paper, a systematic mapping study has been conducted, the aim of which was to discover the main issues dealt with in GSD governance literature, as well as to point out the particular research gaps that are still present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…Our findings showed the companies' KPIs did not measure the success of the distributed teamwork and the quality of the code produced. Governing and measuring in global software development is known to be difficult and research is lacking [41]. Our findings confirm previous research that showed the number of PRs might not be a good measurement for developer productivity [22].…”
Section: Discussionsupporting
confidence: 85%
“…Our findings showed the companies' KPIs did not measure the success of the distributed teamwork and the quality of the code produced. Governing and measuring in global software development is known to be difficult and research is lacking [41]. Our findings confirm previous research that showed the number of PRs might not be a good measurement for developer productivity [22].…”
Section: Discussionsupporting
confidence: 85%
“…However, to scale agile and coordinate development tasks within distributed teams, it is necessary to tailor the agile practices. As presented by Manjavacas et al [139], ensuring and establishing a governance structure for the IT organization, and ensuring stakeholder engagement and participation are the most present governance objectives in the literature on GSD governance. These governance objectives can be achieved through the use of combined practices, and SAFe helps reinforce the governance structure in a software organization.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, governance involves practices and commitments focused on the proper management of the organization. 3,4 Thus, governance activities can be…”
Section: O R P O R At E G Ov E R Na N C Ementioning
confidence: 99%